Rancang Bangun Aplikasi Mobile Kemajuan Akademik Mahasiswa Jurusan Sistem Informasi Pada Fakultas Sains dan Teknologi UIN Alauddin Makassar - Farida Yusuf; Gunawan; Zulfiana Rahman Rahman (Jurnal INSYPRO (Information System and Processing), 2022)
Processing of student progress data is currently done through recording in a book (logbook). This process is carried out by academic advisory lecturers. The purpose of this research is to create a mobile application for the academic progress of students of the Information Systems Department at the Faculty of Science and Technology, UIN Alauddin Makassar. The research method used is qualitative and the application development uses the waterfall method. The Design and Build of Mobile Applications for Student Progress in the Information Systems Department at the Faculty of Science and Technology UIN Alauddin Makassar was created using an android-based programming language with web-based programming (PHP), MySQL, as the database and this system uses the Black Box testing method. The results of this study resulted in a mobile application for the progress of students of the Department of Information Systems at the Faculty of Science and Technology, UIN Alauddin Makassar. Where based on a questionnaire consisting of 10 questions and distributed to 27 respondents, the final result obtained is an average total percentage of 81.2%, which means that respondents strongly agree with this system. Keywords: Mobile Application, Student Progress, PHP, MYSQL